Method for producing lithium cobalt-based composite oxide particles

The thermal decomposition and controlled firing of cobalt compounds produce lithium cobalt-based composite oxide particles with controlled properties, addressing the issue of grain growth in existing methods, enabling lighter and thinner battery materials with improved reactivity and stability.

JP2024176362APending Publication Date: 2024-12-19NIPPON CHEMICAL IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023094848
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing methods for producing lithium cobalt-based composite oxide particles for non-aqueous lithium secondary batteries and all-solid-state batteries result in increased particle size due to grain growth during high-temperature firing, hindering the miniaturization and weight reduction of positive electrode materials.

Method used

A method involving the thermal decomposition of nano-level cobalt compounds, such as cobalt hydroxide or cobalt salts, to produce cobalt oxide, followed by mixing with lithium compounds and firing at lower temperatures to control particle size and prevent grain growth, resulting in lithium cobalt-based composite oxide particles with controlled properties.

Benefits of technology

The method enables the production of lithium cobalt-based composite oxide particles with reduced weight and thickness, suitable for use as positive electrode materials in batteries, with improved reactivity and stability, minimizing defects in the manufacturing process and maintaining charge/discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176362000001_ABST
    Figure 2024176362000001_ABST
Patent Text Reader

Abstract

To provide a method for producing lithium cobalt-based composite oxide particles capable of reducing the weight and thickness of a cathode material when used as a cathode active material for a nonaqueous lithium secondary battery or an all-solid-state battery.SOLUTION: A method for producing lithium cobalt-based composite oxide particles comprises a step of thermally decomposing a raw material cobalt compound having an average particle diameter of 0.05 to 1.00 μm by SEM observation to obtain an oxide of cobalt, wherein the raw material cobalt is cobalt hydroxide or a salt of cobalt, a mixture preparation step of preparing a mixture containing at least a lithium compound and an oxide of cobalt obtained by the thermal decomposition step, and a calcination step of calcining the mixture prepared by the mixture preparation step at 500 to 850°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing lithium-cobalt composite oxide particles useful as a positive electrode material for non-aqueous lithium secondary batteries, all-solid-state batteries, and the like. [Background technology]

[0002] Non-aqueous lithium secondary batteries are used as power sources for portable devices, notebook computers, electric vehicles, industrial robots, etc. In recent years, in place of non-aqueous lithium secondary batteries that use electrolytes containing flammable organic solvents, active development of all-solid-state batteries that use highly safe solid electrolytes has been underway.

[0003] Recently, both non-aqueous lithium secondary batteries and all-solid-state batteries are required to be made lighter and thinner depending on the application. To make batteries lighter and thinner, it is necessary to miniaturize the components that make up the battery. For example, miniaturizing the positive electrode material is one factor that leads to making batteries lighter and thinner.

[0004] Regarding the miniaturization of the positive electrode material, for example, Patent Document 1 describes the 10% particle size (D 10 ) is 0.01μm~0.5μm, 50% particle size (D 50 ) of 0.01 μm to 1.0 μm, and the content of particles having a particle size of 0.12 μm or less is 0.5 vol % or more. Patent Document 1 does not disclose the specific manufacturing method by which the positive electrode active material was obtained, but it is clear that the use of a nano-level positive electrode active material makes it possible to form a thin film of the electrode member.

[0005] As for the creation of nanomaterials from lithium-based composite oxides as positive electrode active materials, Patent Document 2 describes the synthesis of nano-level lithium-based composite oxides using molten salt as a reactant and reaction medium, accompanied by a drying process. This is said to enable the synthesis of improved functionality and the development of new functions compared to conventional larger materials, while also aiming to miniaturize electronic devices. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-220468 A [Patent Document 2] JP 2008-105912 A Summary of the Invention [Problem to be solved by the invention]

[0007] The method of Patent Document 2 utilizes the fact that the raw material metal ions are present in a completely dissociated state in the molten salt and are mixed at the ionic level, so that even with heat treatment at a relatively low temperature, a stable substance is easily formed because it reaches chemical thermodynamic equilibrium.

[0008] However, lithium-cobalt composite oxides are usually obtained by mixing and sintering multiple raw material powders, a process known as the solid-phase method, and in order to fully react the raw material powders, it is necessary to raise the sintering temperature, which promotes crystallization but also causes grain growth, resulting in an increase in the particle size of the lithium-cobalt composite oxide particles, making it difficult to reduce the weight and thickness of the cathode material.

[0009] Therefore, an object of the present invention is to provide a method for producing lithium-cobalt-based composite oxide particles obtained by a solid-phase method, which, when used as a positive electrode active material for a nonaqueous lithium secondary battery or an all-solid-state battery, enables the positive electrode material to be made lighter and thinner. [Means for solving the problem]

[0010] The present inventors have conducted extensive research in light of the above-mentioned circumstances, and as a result have found that cobalt oxide obtained by thermally decomposing a raw material cobalt compound selected from cobalt hydroxide or cobalt salt, which are nano-level fine particles, generates almost no gas during firing, and becomes nano-level fine particles due to the cobalt compound used, and further that by using cobalt oxide, which is a nano-level fine particle obtained by thermally decomposing the raw material cobalt compound, reaction with a lithium compound proceeds easily, and therefore crystallization proceeds well even when fired at a low temperature, thereby completing the present invention.

[0011] That is, the present invention (1) is a process for obtaining an oxide of cobalt by thermally decomposing a raw material cobalt compound having an average particle size of 0.05 to 1.00 μm as determined by SEM observation, in which the raw material cobalt is cobalt hydroxide or a cobalt salt; a mixture preparation step of preparing a mixture containing at least a lithium compound and the oxide of cobalt obtained by the thermal decomposition step; A firing step of firing the mixture prepared by the mixture preparation step at 500 to 850 ° C.; The present invention provides a method for producing lithium-cobalt-based composite oxide particles, which is characterized by having the above-mentioned.

[0012] The present invention (2) also provides a method for producing lithium-cobalt-based composite oxide particles as described in (1), characterized in that the raw material cobalt compound is cobalt hydroxide.

[0013] The present invention (3) also provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that the lithium compound is at least one selected from the group consisting of lithium carbonate, hydroxide, acetate and nitrate.

[0014] The present invention (4) also provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that in the thermal decomposition step, thermal decomposition is carried out at 200 to 1000° C.

[0015] The present invention (5) also provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that the cobalt oxide has an average particle size of 0.05 to 4.00 μm as determined by SEM observation.

[0016] The present invention (6) also provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that, after the calcination step, a calcined product crushing step is carried out to crush the lithium-cobalt-based composite oxide particles obtained by the calcination step.

[0017] The present invention (7) provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing a lithium-cobalt-based composite oxide according to claim 1 or 2 have an average particle size of 0.10 to 5.00 μm as determined by SEM observation, and a weight loss rate of 1.5 mass % or less when heated at 850° C.

[0018] The present invention (8) also provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing a lithium-cobalt-based composite oxide according to claim 1 or 2 have a residual alkali content of 2.0% or less.

[0019] The present invention (9) provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing a lithium-cobalt-based composite oxide according to claim 1 or 2 have a CV value of 0.60 or less of the average particle size as determined by SEM observation, and no impurity phase other than the hexagonal crystal phase (R-3m) derived from the lithium-cobalt-based composite oxide is observed by X-ray diffraction analysis.

[0020] The present invention (10) also provides a method for producing lithium-cobalt-based composite oxide particles according to (1) or (2), characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing a lithium-cobalt-based composite oxide according to claim 1 or 2 are obtained by a solid phase method. Effect of the Invention

[0021] According to the present invention, there can be provided a method for producing lithium-cobalt-based composite oxide particles obtained by a solid phase method, which, when used as a positive electrode active material for a nonaqueous lithium secondary battery or an all-solid-state battery, enables the positive electrode material to be made lighter and thinner. [Brief description of the drawings]

[0022] [Figure 1] 1 is an X-ray diffraction chart of the lithium-cobalt composite oxide particles obtained in Examples 1 to 6. [Diagram 2] 2 is an X-ray diffraction chart of the lithium-cobalt-based composite oxide particles obtained in Examples 7 to 10. [Diagram 3] 2 is an X-ray diffraction chart of the lithium-cobalt-based composite oxide particles obtained in Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present invention will now be described based on preferred embodiments. The method for producing lithium-cobalt-based composite oxide particles of the present invention includes a step of thermally decomposing a raw material cobalt compound having an average particle size of 0.05 to 1.00 μm as determined by SEM observation to obtain an oxide of cobalt, the raw material cobalt being cobalt hydroxide or a cobalt salt; A mixture preparation step of preparing a mixture containing at least a lithium compound and an oxide of a cobalt compound obtained as a thermal decomposition product by the thermal decomposition step; A firing step of firing the mixture prepared by the mixture preparation step at 500 to 850 ° C.; The present invention is characterized by having the following.

[0024] The thermal decomposition step in the method for producing lithium-cobalt-based composite oxide particles of the present invention is a step of using cobalt hydroxide or a cobalt salt as a raw cobalt compound, thermally decomposing the raw cobalt compound to obtain cobalt oxide. That is, it is a step of heating the raw cobalt compound, i.e., cobalt hydroxide or a cobalt salt, to thermally decompose the raw cobalt compound and obtain cobalt oxide as a thermal decomposition product.

[0025] Examples of the raw cobalt compound in the thermal decomposition step include cobalt hydroxide and cobalt salts, such as cobalt carbonates, cobalt organic acid salts, cobalt nitrates, etc. As these raw cobalt compounds, raw cobalt compounds obtained as a thermal decomposition product of cobalt oxides such as tricobalt tetroxide are preferred, since they hardly generate gas when the cobalt compound is fired, which is thought to be one of the factors that inhibit the firing reaction, and they become nano-level fine particles due to the cobalt compound used. Cobalt hydroxide is particularly preferred, since it has a small particle size as a single particle and does not require any adjustment of the particle size by prior grinding treatment or the like.

[0026] The raw material cobalt compound in the thermal decomposition step may have any manufacturing history, but it is preferable that the impurity content is as low as possible in order to produce high-purity lithium-cobalt composite oxide particles.

[0027] The average particle size of the raw material cobalt compound in the thermal decomposition step as determined by SEM is 0.05 to 1.00 μm, preferably 0.05 to 0.50 μm. By determining that the average particle size of the raw material cobalt compound in the thermal decomposition step as determined by SEM is within the above range, the method for producing lithium-cobalt-based composite oxide particles of the present invention can be used to obtain lithium-cobalt-based composite oxide particles having an average particle size of 0.10 to 5.00 μm, preferably 0.10 to 3.50 μm as determined by SEM.

[0028] The decomposition temperature in the decomposition step is not particularly limited as long as it is a temperature at which the raw cobalt compound decomposes. For example, the decomposition temperature in the decomposition step may be 200 to 1000°C. By heating the raw cobalt compound having an average particle size of 0.05 to 1.00 μm, preferably 0.05 to 0.50 μm as measured by SEM, at a temperature at which the raw cobalt compound decomposes, a cobalt oxide having a small CV value (standard deviation / average particle size) in the particle size distribution as measured by SEM observation, that is, a cobalt oxide having a small particle size variation, can be obtained. The obtained cobalt oxide is used to obtain lithium-cobalt composite oxide particles through the subsequent steps, and the lithium-cobalt composite oxide particles having a small CV value can be obtained in the method for producing lithium-cobalt composite oxide particles of the present invention. Therefore, the method for producing lithium-cobalt-based composite oxide particles of the present invention provides lithium-cobalt-based composite oxide particles obtained by a solid-phase method, and when used as a positive electrode active material for a non-aqueous lithium secondary battery or an all-solid-state battery, the positive electrode material is less likely to have defects in the positive electrode material production process, and the positive electrode material can be made lighter and thinner. Furthermore, in the method for producing lithium-cobalt-based composite oxide particles of the present invention, by using a cobalt oxide with a small CV value, there is no variation in reactivity, and therefore, even when the firing temperature is relatively low, lithium-cobalt-based composite oxide particles can be obtained that are free of impurity phases other than the hexagonal crystal phase (R-3m) derived from the lithium-cobalt-based composite oxide when analyzed by X-ray diffraction using CuKα radiation as a radiation source.

[0029] The hexagonal crystal phase (R-3m) derived from the lithium-cobalt composite oxide indicates diffraction peaks observed at 2θ=18.9° (18.9±0.2°), 37.4° (37.4±0.2°), 38.4° (38.4±0.2°), 39.1° (39.1±0.2°), 45.3° (45.3±0.2°), 49.5° (49.5±0.2°), 59.6° (59.6±0.2°), 65.5° (65.5±0.2°), 66.4° (66.4±0.2°), 69.8° (69.8±0.2°), etc., which are due to LiCoO2. The impurity phase indicates diffraction peaks other than those due to LiCoO2. Specific examples of such impurity phases include cobalt oxide (Co3O4) having a main peak around 36.8° (36.8±0.2°), lithium carbonate (Li2CO3) having a main peak around 31.8° (31.8±0.2°), and cubic lithium-cobalt composite oxide (LiCoO2 cubic crystal) having a main peak around 19.2° (19.2±0.2°).

[0030] The decomposition temperature in the decomposition step is 200 to 1000°C, preferably 200 to 850°C, more preferably 200 to 700°C. By using the decomposition temperature in the decomposition step within the above range, it is possible to obtain cobalt oxide having a small CV value in the particle size distribution observed by SEM, and by using the obtained cobalt oxide to obtain lithium-cobalt composite oxide particles through the subsequent steps, the method for producing lithium-cobalt composite oxide particles of the present invention can obtain lithium-cobalt composite oxide particles having a small CV value in the particle size distribution observed by SEM. Therefore, in the method for producing lithium-cobalt composite oxide particles of the present invention, by using the decomposition temperature in the decomposition step within the above range, when the lithium-cobalt composite oxide particles obtained by the solid phase method are used as a positive electrode active material for a non-aqueous lithium secondary battery or an all-solid-state battery, the effect of making the positive electrode material less likely to cause defects in the positive electrode material production step and making it easier to make the positive electrode material lighter and thinner is enhanced. In addition, when the temperature of the thermal decomposition step is, for example, 200 to 700 ° C., it is easy to obtain cobalt oxide while suppressing the coarsening of the raw material cobalt compound, so that it is possible to obtain cobalt oxide having a small average particle diameter of 0.05 to 1.50 μm, preferably 0.05 to 1.00 μm as measured by SEM observation. By using the obtained cobalt oxide through the subsequent steps to obtain lithium-cobalt composite oxide particles, the method for producing lithium-cobalt composite oxide particles of the present invention can obtain lithium-cobalt composite oxide particles having a small average particle diameter of 0.10 to 2.00 μm, preferably 0.10 to 1.00 μm as measured by SEM observation. Therefore, when the lithium-cobalt composite oxide particles are used as a positive electrode active material for non-aqueous lithium secondary batteries or all-solid-state batteries, it is possible to provide a method for producing lithium-cobalt composite oxide particles that can reduce the weight and thickness of the positive electrode material.

[0031] The thermal decomposition time in the thermal decomposition step is 1 to 10 hours, preferably 2 to 5 hours. The thermal decomposition atmosphere in the thermal decomposition step is preferably an oxidizing atmosphere such as air or oxygen gas.

[0032] The oxides of cobalt obtained by carrying out the thermal decomposition step include Co3O4, CoO, Co2O3, etc., with Co3O4 being preferred.

[0033] The average particle size of the cobalt oxide obtained by carrying out the thermal decomposition step, as determined by SEM observation, is 0.05 to 4.00 μm, and preferably 0.05 to 3.00 μm. By having the average particle size of the cobalt oxide obtained by carrying out the thermal decomposition step within the above range, it is possible to obtain, through the subsequent steps, lithium-cobalt-based composite oxide particles having an average particle size, as determined by SEM observation, of 0.10 to 5.00 μm, and preferably 0.10 to 3.50 μm.

[0034] The CV value (standard deviation / average particle size) in the particle size distribution of the cobalt oxide obtained in the thermal decomposition step as determined by SEM observation is 0.60 or less, preferably 0.50 or less, and particularly preferably 0.40 or less. By having the CV value of the cobalt oxide obtained in the thermal decomposition step within the above range, it is possible to obtain, through subsequent steps, lithium-cobalt-based composite oxide particles having a CV value in the particle size distribution as determined by SEM observation of 0.60 or less, preferably 0.50 or less, and particularly preferably 0.45 or less.

[0035] In the present invention, the average particle diameters in SEM observation of the raw material cobalt compound in the thermal decomposition step, the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention, the cobalt oxide obtained by carrying out the thermal decomposition step, and the lithium compound are, unless otherwise specified, the average particle diameters of primary particles determined from scanning electron microscope (SEM) photographs, and 100 primary particles are arbitrarily extracted from the scanning electron microscope (SEM) observation, the horizontal Feret diameter of each particle is measured, and the average value of the 100 particles is determined as the average particle diameter of the primary particles. In the present invention, the standard deviation and CV value of the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention and of the oxide of cobalt obtained by carrying out the thermal decomposition step are, unless otherwise specified, the standard deviation and CV value of the primary particles obtained from a scanning electron microscope (SEM) photograph, and are obtained by randomly extracting 100 primary particles from scanning electron microscope (SEM) observation, measuring the horizontal Feret diameter of each particle, determining the particle diameters of the 100 primary particles, and determining the average particle diameter, standard deviation and CV value from the particle size distribution of the obtained 100 particles.

[0036] The mixture preparation step in the method for producing lithium-cobalt-based composite oxide particles of the present invention is a step of preparing a mixture containing at least a lithium compound and an oxide of cobalt obtained by the thermal decomposition step.

[0037] The lithium compound in the mixture preparation step is not particularly limited as long as it is a lithium compound that can be used as a raw material for producing lithium-cobalt-based composite oxide particles, and examples of the lithium compound include oxides, hydroxides, carbonates, nitrates, sulfates, and organic acid salts of lithium.

[0038] The lithium compound in the mixture preparation step has an average particle size of 0.1 to 100.0 μm, preferably 0.1 to 10.0 μm, and particularly preferably 0.1 to 1.0 μm, as determined by SEM observation. When the average particle size of the lithium compound in the mixture preparation step is within the above range as determined by SEM observation, uniformity can be achieved during firing, making it easier to obtain single-phase lithium-cobalt composite oxide particles.

[0039] In the mixture preparation step, the lithium compound and the cobalt oxide are adjusted so that the molar ratio of Li to Co in the mixture (Li / Co) in atomic terms is 0.90 to 1.20, preferably 0.95 to 1.15. When the molar ratio of Li to Co in the mixture (Li / Co) in atomic terms is within the above range, single-phase lithium-cobalt composite oxide particles are easily obtained.

[0040] In the mixture preparation step, a compound containing an M element may be added to the mixture as necessary. Examples of the compound containing an M element include oxides, hydroxides, carbonates, nitrates, sulfates, fluorides, and organic acid salts containing an M element. As the compound containing an M element, a compound containing two or more kinds of M elements may be used. Examples of the M element include one or more kinds of Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, K, Ni, and Mn.

[0041] In the mixture preparation step, when a compound containing an M element is added to the mixture as necessary, the molar percentage of the M element relative to Co in the mixture ((M / Co)×100) in atomic terms is adjusted to be preferably 0.01 to 5.00 molar percentage, particularly preferably 0.05 to 2.00 molar percentage. When the molar percentage of the M element relative to Co in the mixture ((M / Co)×100) in atomic terms is within the above range, lithium cobalt-based composite oxide particles can be obtained that can improve battery characteristics without impairing charge / discharge capacity. Note that, when the mixture contains two or more kinds of M elements, the number of moles of the M element in atomic terms, which is the basis for calculating the above molar percentage, refers to the total number of moles of each M element.

[0042] In the mixture preparation step, the lithium compound and the compound containing the M element may have any manufacturing history, but in order to produce high-purity lithium-cobalt-based composite oxide particles, it is preferable that the impurity content is as low as possible.

[0043] In the mixture preparation step, a lithium compound, an oxide of cobalt, and an optionally used compound containing an M element are mixed in a dry or wet manner to prepare a mixture. At this time, the cobalt oxide in the mixture is present so that the average particle size by SEM observation is 0.05 to 4.00 μm, preferably 0.05 to 3.00 μm, and the lithium compound and the compound containing the M element used as required are mixed by stirring, grinding, etc. This mixing facilitates contact between the lithium compound, the cobalt oxide, and the compound containing the M element used as required. By having the average particle size by SEM observation of the cobalt oxide in the mixture within the above range, the reactivity of the mixture in the firing step can be increased, and the reaction can be sufficiently promoted even when firing at a low temperature of, for example, 500 to 850 ° C.

[0044] In the present production method, when the mixing treatment is carried out in the mixture preparation step, particle size adjustment may be carried out. The mixing treatment may also serve as a pulverization treatment. For example, (i) a method of pulverizing the cobalt oxide to adjust the particle size before mixing the lithium compound, the cobalt oxide, and the compound containing the M element used as necessary, and then mixing the pulverized cobalt oxide, the lithium compound, and the compound containing the M element used as necessary; (ii) a method of pulverizing the lithium compound to adjust the particle size before mixing the lithium compound, the cobalt oxide, and the compound containing the M element used as necessary, and then mixing the pulverized lithium compound, the cobalt oxide, and the compound containing the M element used as necessary; (iii) a method of pulverizing the cobalt oxide before mixing the lithium compound, the cobalt oxide, and the compound containing the M element used as necessary, and further pulverizing the lithium compound and / or the compound containing the M element, and mixing the pulverized cobalt oxide, the lithium compound, and the compound containing the M element used as necessary; and (iv) a method of mixing the lithium compound, the cobalt oxide, and the compound containing the M element used as necessary, and then mixing and pulverizing them.

[0045] The grinding process of the cobalt oxide, the lithium compound, or the compound containing the M element, and the mixed grinding process of the cobalt oxide, the lithium compound, and the compound containing the M element used as needed may be a dry process or a wet process.

[0046] Examples of the apparatus for performing the dry mixing treatment, pulverization treatment, or mixed pulverization treatment include a jet mill, a pin mill, a roll mill, a ball mill, a bead mill, etc. Also, at the laboratory level, a tabletop mixer may be used. Examples of the apparatus for performing the wet mixing treatment, pulverization treatment, or mixed pulverization treatment include a ball mill, a bead mill, etc.

[0047] When the mixture is prepared in a wet state, it is preferable to dry the mixture. The drying method is performed in a conventional manner, but when the mixture is mixed, crushed, or mixed and crushed in a wet state, for example, a method using a spray dryer can be applied.

[0048] The calcination step in the method for producing lithium-cobalt-based composite oxide particles of the present invention is a step of obtaining lithium-cobalt-based composite oxide particles by calcining the mixture prepared in the mixture preparation step.

[0049] The firing temperature in the firing step is 500 to 850° C., preferably 550 to 800° C. By using the firing temperature in the firing step within the above range, it is possible to obtain lithium-cobalt-based composite oxide particles that can reduce the weight and thickness of the positive electrode material when used as a positive electrode active material for a nonaqueous lithium secondary battery or an all-solid-state battery. Although the grain growth in the sintering step can be suppressed by lowering the sintering temperature in the sintering step, if the sintering temperature in the sintering step is too low in an attempt to suppress the grain growth, the reaction of the mixture becomes insufficient. If such lithium-cobalt-based composite oxide particles in which the reaction of the mixture is insufficient are used, not only will the cathode material preparation step cause a defect, but the charge / discharge capacity expected of the lithium-cobalt-based composite oxide particles will decrease. In contrast, the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention are produced by increasing the reactivity of the mixture in the sintering step through a thermal decomposition step and a mixture preparation step, so the reaction has progressed sufficiently, and there is no defect in the cathode material preparation step or a decrease in the charge / discharge capacity expected of the lithium-cobalt-based composite oxide particles.

[0050] Furthermore, it is particularly preferred that the firing temperature in the firing step is 500 to 850°C, preferably 550 to 800°C, in that when X-ray diffraction analysis is performed using CuKα radiation as a radiation source, lithium-cobalt-based composite oxide particles are obtained that are free of impurity phases other than the hexagonal crystal phase (R-3m) derived from the lithium-cobalt-based composite oxide.

[0051] The firing time in the firing step is 1 to 30 hours, preferably 3 to 20 hours. The firing atmosphere in the firing step is an oxidizing atmosphere such as air, oxygen gas, etc. In the firing step, the fired product obtained in the first firing may be fired multiple times as necessary.

[0052] In the method for producing lithium-cobalt-based composite oxide particles of the present invention, if necessary, after the calcination step, a calcined product crushing step can be carried out in which the lithium-cobalt-based composite oxide particles obtained by the calcination step are crushed.

[0053] The pulverization process in the sintered product pulverization process may be a dry pulverization process or a wet pulverization process. Examples of wet pulverization devices include ball mills and bead mills. Examples of dry pulverization devices include known pulverization devices such as jet mills, pin mills, roll mills, ball mills, and bead mills.

[0054] The preferred physical properties of the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention are that the lithium-cobalt-based composite oxide particles are free of impurity phases other than the hexagonal crystal phase (R-3m) derived from the lithium-cobalt-based composite oxide when analyzed by X-ray diffraction using CuKα radiation as a radiation source, and that the average particle size as determined by SEM observation is 0.10 to 5.00 μm, preferably 0.10 to 3.50 μm. When the average particle size of the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention is within the above range, it becomes easier to make the positive electrode material lighter and thinner, and therefore easier to make the battery smaller.

[0055] The CV value of the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention is not more than 0.60, preferably not more than 0.50, and particularly preferably not more than 0.45. When the CV value of the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention is in the above range, the variation in particle size is reduced, and therefore defects are less likely to occur in the positive electrode material production process, and the positive electrode material can be made lighter and thinner.

[0056] Furthermore, the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention have a weight loss rate of 1.5% by mass or less, preferably 1.0% by mass or less, and particularly preferably 0.5% by mass or less when heated at 850° C. When the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention have a weight loss rate of 1.5% by mass or less when heated at 850° C., the reaction proceeds sufficiently, and therefore defects in the positive electrode material production process and a decrease in the charge / discharge capacity expected of the lithium-cobalt-based composite oxide are unlikely to occur.

[0057] In the present invention, the weight loss rate when heated at 850° C. is a value calculated by the following formula. Weight reduction rate (%)=((XY) / X)×100 X indicates the mass (g) of the lithium-cobalt-based composite oxide particles before heating at 850°C. Y indicates the mass (g) of the lithium-cobalt-based composite oxide particles that have been heated to 850°C at a heating rate of 100°C / hour, held at 850°C for 5 hours, and then cooled naturally to room temperature.

[0058] Furthermore, the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention have a residual alkali content of 2.0% or less, preferably 1.0% or less. When the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention have a residual alkali content within the above range, the slurry stability of the paint when applied to the electrode is improved, and the effect of making it easier to make the cathode material thinner is enhanced.

[0059] In the present invention, the residual alkali amount refers to an alkali component that is dissolved in water when the lithium-cobalt composite oxide particles, which are the measurement sample, are dispersed in water at 25° C. and stirred. Examples of the alkali component include lithium carbonate (Li2CO3) and lithium hydroxide (LiOH). The amount of residual alkali is calculated by measuring 2 g of lithium-cobalt composite oxide particles and 50 g of ultrapure water in a beaker, dispersing and stirring the mixture with a magnetic stirrer at 25°C for 5 minutes, filtering the dispersion, and subjecting the amount of alkali present in the filtrate to neutralization titration. The amount of residual alkali is a value obtained by measuring the amount of lithium by titration and converting it into lithium carbonate (Li2CO3).

[0060] The lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention are lithium-cobalt-based composite oxide particles obtained by a solid phase method.

[0061] Furthermore, the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention are composed of primary particles of the lithium-cobalt-based composite oxide, or are composed of secondary particles formed by aggregation of primary particles of the lithium-cobalt-based composite oxide, or are composed of a mixture of primary particles and secondary particles of the lithium-cobalt-based composite oxide.

[0062] Furthermore, the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention are suitably used as a positive electrode active material for lithium secondary batteries, all-solid-state batteries, and the like.

[0063] In order to further improve the sinterability of the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention, a lithium-containing compound can be further mixed and contained to form a lithium-cobalt-based composite oxide particle composition containing the lithium-cobalt-based composite oxide particles of the present invention and the lithium-containing compound.

[0064] Examples of the lithium-containing compound for the lithium-cobalt-based composite oxide particle composition include lithium carbonate, lithium hydroxide, and lithium nitrate.

[0065] The lithium-containing compound to be mixed with the lithium-cobalt composite oxide particles has an average particle size of 0.10 to 100.0 μm, preferably 0.10 to 10.0 μm, and more preferably 0.10 to 1.0 μm. When the average particle size of the lithium-containing compound is within the above range, it becomes easy to uniformly disperse the lithium-containing compound in the lithium-cobalt composite oxide particle composition, which is preferable from the viewpoint of enabling sintering at a lower temperature.

[0066] In the lithium-cobalt composite oxide particle composition, the content of the lithium-containing compound is 0.01 to 10.0 mass %, preferably 0.05 to 5.0 mass %, calculated as lithium atoms relative to the mass of the lithium-cobalt composite oxide particles. The content of the lithium-containing compound in the above range is preferable from the viewpoint of enabling sintering at a lower temperature.

[0067] The method for mixing the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide particles of the present invention with a lithium-containing compound is not particularly limited as long as the respective components can be mixed uniformly, and may be a dry method or a wet method. EXAMPLES

[0068] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0069] (1) Average particle size, standard deviation, and CV value by SEM observation One hundred primary particles were randomly selected from the particles to be measured using a scanning electron microscope (SEM), the horizontal Feret diameter of each particle was measured, and the average particle diameter was calculated from the average value of the 100 particles. 100 primary particles were randomly selected from the scanning electron microscope (SEM) observation of the particles to be measured, the horizontal Feret diameter of each particle was measured, and the standard deviation and CV value were calculated based on the particle size distribution obtained from the particle diameters of the 100 particles. The CV value was calculated using the formula "CV value = standard deviation / average particle size". (2) Weight loss rate when heated at 850℃ It was calculated using the following formula. Weight reduction rate (%)=((XY) / X)×100 X: Mass of lithium-cobalt composite oxide particles before heating at 850°C (g) Y: Mass (g) of lithium-cobalt-based composite oxide particles that have been heated to 850°C at a heating rate of 100°C / hour, held at 850°C for 5 hours, and then cooled to room temperature by natural cooling. (3) Residual alkali content of lithium-cobalt composite oxide particles 2 g of lithium-cobalt composite oxide particles and 50 g of pure water were weighed into a beaker and dispersed using a magnetic stirrer for 5 minutes at 25° C. Next, this dispersion was filtered, and 30 ml of the filtrate was titrated with 0.1N-HCl using an automatic titrator (COMTITE-2500) to calculate the amount of residual alkali present in the sample (a value calculated by measuring the amount of lithium and converting it into lithium carbonate). (4) Crystal phase The measurements were performed using an X-ray diffractometer (Rigaku Corporation, Ultima IV) using Cu-Kα radiation as the radiation source. (5) D50 The particle size distribution of the particles to be measured was measured by the laser diffraction / scattering method using water as the measurement solvent. The particle size at 50% of the volumetric conversion of the obtained particle size distribution was taken as D50 of the particles to be measured.

[0070] (Examples 1 to 6) (Thermal decomposition process) Cobalt hydroxide (average particle size 0.17 μm as observed by SEM) was thermally decomposed at 300°C for 3 hours to obtain cobalt oxide (Co3O4) with an average particle size of 0.16 μm as observed by SEM. (Mixture preparation process) The obtained pyrolysis product (Co3O4, average particle size by SEM observation: 0.16 μm) and lithium carbonate (average particle size by SEM observation: 7.0 μm) were weighed out so that the Li / Co ratio was 1.00, and then dry-mixed and ground in a commercially available tabletop mixer to obtain 10.0 g of a mixture. (Firing process) The obtained mixture was calcined for 5 hours at the calcination temperature shown in Table 1 to obtain lithium-cobalt-based composite oxide particles. The obtained lithium-cobalt-based composite oxide particles were crushed for 30 seconds in a tabletop mixer to obtain lithium-cobalt-based composite oxide particles. (Cinder crushing process) The obtained lithium-cobalt-based composite oxide particles were subjected to airflow pulverization in a jet mill (AO Jet Mill, manufactured by Seishin Enterprise Co., Ltd.) with P pressure set at 0.65 MPa and J pressure set at 0.60 MPa and a feed rate of 2 g / min to obtain lithium-cobalt-based composite oxide particles. The physical properties of the obtained lithium-cobalt-based composite oxide particles are shown in Table 1. Furthermore, the weight loss rate of the obtained lithium-cobalt-based composite oxide particles when heated at 850°C was 1.0 mass% or less in all cases.

[0071] (Examples 7 to 10) (Thermal decomposition process) Cobalt hydroxide (average particle size 0.17 μm as observed by SEM) was thermally decomposed at 300°C for 3 hours to obtain cobalt oxide (Co3O4) with an average particle size of 0.16 μm as observed by SEM. (Mixture preparation process) Pure water was added to lithium carbonate (average particle size 7.0 μm as observed by SEM) to make the slurry concentration 20 mass%, and the mixture was wet-mixed and ground in a bead mill (LMZ22, manufactured by Ashizawa Finetech Co., Ltd.) using Zr balls of φ0.5 mm to obtain lithium carbonate slurry. The obtained lithium carbonate slurry was spray-dried in a spray dryer (L-8, manufactured by Okawara Kakoki Co., Ltd.) with an inlet temperature of 250 ° C and an outlet temperature of 120 ° C and a feed rate of 60 g / min, and then air-flow ground in a jet mill (AO jet mill, manufactured by Seishin Enterprise Co., Ltd.) with a P pressure of 0.65 MPa and a J pressure of 0.60 MPa and a feed rate of 2 g / min to obtain fine lithium carbonate particles with an average particle size of 0.48 μm as observed by SEM. Next, the obtained pyrolysis product (Co3O4, average particle size as observed by SEM: 0.16 μm) and the obtained fine lithium carbonate (average particle size as observed by SEM: 0.48 μm) were weighed out so that the Li / Co ratio was 1.00, and were dry mixed and ground in a commercially available tabletop mixer to obtain 10.0 g of a mixture. (Firing process) The obtained mixture was calcined for 5 hours at the calcination temperature shown in Table 1 to obtain lithium-cobalt-based composite oxide particles. The obtained lithium-cobalt-based composite oxide particles were crushed for 30 seconds in a tabletop mixer to obtain lithium-cobalt-based composite oxide particles. (Cinder crushing process) The obtained lithium-cobalt-based composite oxide particles were subjected to airflow pulverization in a jet mill (AO Jet Mill, manufactured by Seishin Enterprise Co., Ltd.) with P pressure set at 0.65 MPa and J pressure set at 0.60 MPa and a feed rate of 2 g / min to obtain lithium-cobalt-based composite oxide particles. The physical properties of the obtained lithium-cobalt-based composite oxide particles are shown in Table 1. Furthermore, the weight loss rate of the obtained lithium-cobalt-based composite oxide particles when heated at 850°C was 0.5 mass% or less in all cases.

[0072] (Comparative Examples 1 to 2) (Mixture preparation process) Cobalt hydroxide (average particle size 0.17 μm as observed by SEM) and lithium carbonate (average particle size 7.0 μm as observed by SEM) were weighed out so that the Li / Co ratio was 1.00, and then dry-mixed and ground in a commercially available tabletop mixer to obtain 10.0 g of a raw material mixture. (Firing process) The resulting raw material mixture was fired for 5 hours at the firing temperature shown in Table 1 to obtain lithium-cobalt-based composite oxide particles. The resulting lithium-cobalt-based composite oxide particles were crushed in a tabletop mixer for 30 seconds to obtain lithium-cobalt-based composite oxide particles. (Cinder crushing process) The obtained lithium-cobalt-based composite oxide particles were subjected to airflow pulverization in a jet mill (AO Jet Mill, manufactured by Seishin Enterprise Co., Ltd.) with P pressure set at 0.65 MPa and J pressure set at 0.60 MPa and a feed rate of 2 g / min to obtain lithium-cobalt-based composite oxide particles. The physical properties of the obtained lithium-cobalt-based composite oxide particles are shown in Table 1. That is, in Comparative Examples 1 and 2, no thermal decomposition step was carried out.

[0073] [Table 1]

[0074] [Table 2]

[0075] From the results in Table 2, it was confirmed that the lithium-cobalt composite oxide particles obtained in Examples 1 to 10 had a small average particle size and a reduced amount of residual alkali compared to those in Comparative Examples 1 and 2. Furthermore, from Figures 1 and 2, it was confirmed that the crystal phase in all of the Examples was a hexagonal single phase. Moreover, in Examples 1, 2, and 7, it was confirmed that the crystal phase was a LCO hexagonal single phase even in those fired at low temperatures of 550 to 600°C. On the other hand, it was confirmed from FIG. 3 that the lithium-cobalt-based composite oxide particles obtained in Comparative Examples 1 and 2 were a mixed phase of hexagonal LCO crystals and tricobalt tetroxide.

[0076] (Examples 11 to 13) Cobalt oxide was obtained by the same thermal decomposition step as in Examples 1 to 6, except that in the thermal decomposition step, cobalt hydroxide (average particle size 0.17 μm as determined by SEM observation) was thermally decomposed at the temperature shown in Table 3. Lithium-cobalt composite oxide particles were then obtained by carrying out a mixture preparation step, a firing step (firing temperature 700° C.), and a firing product pulverization step. The physical properties of the obtained cobalt oxide and lithium-cobalt composite oxide particles are shown in Table 3.

[0077] Comparative Example 3 Except for using commercially available cobalt oxide (average particle size 0.62 μm, standard deviation 0.46, CV value 0.75 as determined by SEM observation) instead of cobalt hydroxide, the mixture preparation step, the firing step (firing temperature 700° C.) and the fired product pulverization step were carried out in the same manner as in Comparative Examples 1 and 2 to obtain lithium-cobalt-based composite oxide particles. The physical properties of the obtained lithium-cobalt-based composite oxide particles are shown in Table 3. That is, in Comparative Example 3, the thermal decomposition step was not carried out.

[0078] [Table 3]

Claims

1. a thermal decomposition step of obtaining an oxide of cobalt by thermally decomposing a raw material cobalt compound having an average particle size of 0.05 to 1.00 μm as determined by SEM observation, in which the raw material cobalt is cobalt hydroxide or a salt of cobalt; a mixture preparation step of preparing a mixture containing at least a lithium compound and the oxide of cobalt obtained by the thermal decomposition step; a firing step of firing the mixture prepared by the mixture preparation step at 500 to 850°C; The present invention relates to a method for producing lithium-cobalt based composite oxide particles.

2. 2. The method for producing lithium-cobalt based composite oxide particles according to claim 1, wherein the raw material cobalt compound is cobalt hydroxide.

3. 3. The method for producing lithium-cobalt-based composite oxide particles according to claim 1, wherein the lithium compound is at least one selected from the group consisting of lithium carbonate, hydroxide, acetate and nitrate.

4. 3. The method for producing lithium-cobalt-based composite oxide particles according to claim 1, wherein the thermal decomposition step is carried out at a temperature of 200 to 1000° C.

5. 3. The method for producing lithium-cobalt-based composite oxide particles according to claim 1, wherein the cobalt oxide has an average particle size of 0.05 to 4.00 μm as determined by SEM observation.

6. 3. The method for producing lithium-cobalt-based composite oxide particles according to claim 1, further comprising the step of: conducting a calcination crushing step of crushing the lithium-cobalt-based composite oxide particles obtained by said calcination step after said calcination step.

7. 3. The method for producing lithium-cobalt-based composite oxide particles according to claim 1 or 2, characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing a lithium-cobalt-based composite oxide according to claim 1 or 2 have an average particle size of 0.10 to 5.00 μm as determined by SEM observation, and a weight loss rate of 1.5 mass % or less when heated at 850° C.

8. 3. The method for producing lithium-cobalt-based composite oxide particles according to claim 1 or 2, characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide according to claim 1 or 2 have a residual alkali content of 2.0% or less.

9. The method for producing lithium-cobalt-based composite oxide particles according to claim 1 or 2, characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing a lithium-cobalt-based composite oxide according to claim 1 or 2 have a CV value of an average particle size of 0.60 or less as determined by SEM observation, and no impurity phase other than the hexagonal crystal phase (R-3m) derived from the lithium-cobalt-based composite oxide is observed by X-ray diffraction analysis.

10. 3. The method for producing lithium-cobalt-based composite oxide particles according to claim 1 or 2, characterized in that the lithium-cobalt-based composite oxide particles obtained by carrying out the method for producing lithium-cobalt-based composite oxide according to claim 1 or 2 are obtained by a solid phase method.

Citation Information

Patent Citations

  • METHOD FOR PRODUCING NANO-MULTIPLE OXIDE AxMyOz

    JP2008105912A

  • Electrode member, all-solid battery, powder for electrode member, manufacturing method of the electrode member, and manufacturing method of the all-solid battery

    JP2019220468A